2013
DOI: 10.1007/s10735-013-9559-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of laminin 5, laminin 10, type IV collagen, and amelotin in adult murine gingiva

Abstract: The biochemical composition of the internal and external basal laminae in the junctional epithelium differs significantly, and the precise cellular origin of their respective molecules remains to be determined. In the present study, the expression and localization of three basement membrane-specific molecules-laminin 5 (γ2 chain), type IV collagen (α1 chain), and laminin 10 (α5 chain)-and one tooth-specific molecule, amelotin, was analyzed in adult murine gingiva by using in situ hybridization and immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It remains to be demonstrated whether AMTN is transcribed and secreted by gingival connective tissue cells or by cells of the gingival epithelium. In any event, the transcription level of AMTN has been found to be too low for detection by in situ hybridization (8,25), and therefore this issue remains beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 84%
“…It remains to be demonstrated whether AMTN is transcribed and secreted by gingival connective tissue cells or by cells of the gingival epithelium. In any event, the transcription level of AMTN has been found to be too low for detection by in situ hybridization (8,25), and therefore this issue remains beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 84%
“…The difference in outcome at the level of the JE between Odam and Amtn KO may reflect the fact that ODAM is not only found at cell-tooth interfaces but is also continuously present among the cells of the JE. Indeed, AMTN may only be transiently expressed in the JE (Sawada et al, 2014) and actually appears late during JE regeneration (Nishio et al, 2010). Like other MPs (Roberts, 2011), it would be expected that the activity of ODAM is contextual, which would explain the increase in severity of the JE phenotype with age in the KO and delay in regeneration following gingivectomy.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier series of immunohistochemical experiments revealed that the internal basal lamina contains laminin 332 [13,[15][16][17][18][19], but no other basement membrane-specific molecules such as type IV collagen [15,[23][24][25], laminin 1/10 [15,19], perlecan [19], or nidogen [15]. At the ultrastructural level using immunoperoxidase labeling, Atsuta et al [20] demonstrated laminin 332 on the internal basal lamina (mainly on the lamina densa and scantly on the lamina lucida) in rat molar gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…ab14509; dilution 1:100; Abcam, Cambridge, UK), overnight at 4°C in a moist chamber. This antibody has been shown to exhibit cross-reactivity with non-human animal tissue [17,18]. In the negative controls, the primary antibody was replaced with PBS.…”
Section: Pre-embedding Immunoperoxidase Labelingmentioning
confidence: 99%
See 1 more Smart Citation